Mechanical matching between a ligand and receptor - Peñaherrera Pazmiño, Ana Belén (2015)
Interactions between ligands and receptors and subsequent ?locking? must involve some resistance to unbinding, manifesting itself as an interaction force. At body temperature, spontaneous unbinding will occur, however, external forces are required to accelerate this process. Bearing in mind the potential forces that the receptor?ligand complex is likely to be subjected to in a biological environment, it might be hypothesised that there is some mechanical matching between the receptor and ligand. To test this hypothesis, various receptor and ligand pairs were unfolded in their entirety in order to determine their total unfolding force. In this way, the total force to unfold the protein could be determined, allowing a comparison between ligand and receptor pairs. The interest of this work is to examine the interaction between five proteins and a mica surface by AFM without any modification to preserve the natural elastic properties of the protein molecules during the force measurements. The results showed a mechanical matching between GP120 (ligand) and CD4 (receptor) when analysing the total force required to unfold the same number of domains or events shown by the force distance curves of these proteins.